PENGARUH KECERDASAN SOSIAL TERHADAP INTERAKSI SOSIAL REMAJA DI LINGKUNGAN SMP NEGERI 10 SEMARANG - Hidayah, Nurul; Handayani, Arri; Dhyah Yulianti, Padmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of social intelligence on social interaction among adolescents at SMP Negeri 10 Semarang. Social intelligence is defined as an individual’s ability to understand others' feelings and social conditions, subsequently adjusting their behavior according to theories by Thorndike, Gardner, and Goleman. Social interaction is a crucial aspect of adolescent development, fostering friendships, empathy, and adaptability in school. Using a quantitative approach with simple linear regression, data were collected via questionnaires from the research sample. The results indicate a significant positive influence of social intelligence on social interaction (p = 0.000 < 0.05). The regression coefficient of 0.971 confirms that higher social intelligence leads to better social interaction quality. Furthermore, the R-Square value of 0.587 shows that social intelligence contributes 58.7% to social interaction, while the remaining 41.3% is influenced by external factors. These findings underscore the importance of social intelligence in enhancing the quality of adolescent social relations within the school environment.